An experimental study of laser cutting of PLA-wood flour 3D printed plates using a modified Taguchi design. (30th May 2023) - Kechagias, John D.; Ninikas, Konstantinos; Salonitis, Konstantinos
Wooden powder flour blended with thermoplastic polylactic acid (WPLA) is an eco-friendly composite material used in filament material extrusion (MEX) additive manufacturing (AM). This work investigates the effect of CO2 laser cutting (LC) of filament MEX WPLA thin plates with variable cutting parameters on mean kerf width (Wm) and means surface roughness (Ra). The experimental design consists of three parameters with three levels each, i.e., the beam cutting direction (CD: 0, 45, 90°), the cutting speed (CS: 8, 13, 18 mm/s), and the beam power (BP: 82.5, 90, 97.5 W). Eleven experiments were performed following the Taguchi L9 orthogonal array plus two in the central point. Finally, additional combinations were run and validated the suggested modified Taguchi design resulting in acceptable mean average percentage errors (MAPE). The optimum parameters' values combination (90° CD, 18mm/s CS and 97.5W BP) results in about 8.44 μm Ra and 0.355 mm Wm.